Crack propensity of different fiber-reinforced direct restorative procedures in deep MOD cavities - Jakab, András Gábor; Néma, Viktória; Molnár, Janka; Alföldi, Aliz; Braunitzer, Gábor; Palkovics, Dániel; Lassila, Lippo; Garoushi, Sufyan; Lempel, Edina; Fráter, Márk (Elsevier BV, 2025)
Objective: The aim of this study was to evaluate crack formation associated with different direct restorative procedures at various time points.
Methods: This in vitro study included 100 intact third molars with standardized MOD cavities, divided into five groups (n = 20). After adhesive treatment, the cavities were restored as follows: bulk-fill flowable short fiber-reinforced composite (SFRC) (Group 1); conventional flowable resin composite (RC) base and bulk-fill flowable SFRC (Group 2); polyethylene fibers embedded in flowable RC and bulk-fill flowable SFRC (Group 3); flowable SFRC combined with packable SFRC (Group 4); and layered conventional packable RC (control). The presence and orientation (vertical/horizontal) of tooth cracks after restoration were evaluated using the D-light Pro (GC Europe) in "detection mode." Cracks were examined at three distinct time points: immediately, after one week, and after five weeks of water storage. The Kruskal-Wallis and Dwass-Steel-Critchlow-Fligner tests were used for between- and within-group comparisons, respectively.
Results: No statistically significant difference in overall crack formation was observed between the groups immediately after the restorative procedure. At the one-week and five-week evaluations, the control group exhibited a significantly higher number of cracks compared to Groups 1-3 (p < 0.01). All groups demonstrated a significantly higher number of cracks at the five-week evaluation compared to the immediate assessment (p < 0.05). The SFRC groups predominantly showed horizontal cracks at all time points.
Significance: In the 5-week period of water storage following polymerization, the number of cracks appearing on the tooth gradually increased, but the flowable SFRC inserted using the bulk technique was able to moderate the phenomenon in MOD cavities.